Regulation of Macrophage, Dendritic Cell, and Microglial Phenotype and Function by the SOCS Proteins - McCormick, Sarah M.; Heller, Nicola M. (Frontiers in Immunology, 2015)
Macrophages are innate immune cells of dynamic phenotype that rapidly respond to external stimuli in the microenvironment by altering their phenotype to respond to and to direct the immune response. The ability to dynamically change phenotype must be carefully regulated to prevent uncontrolled inflammatory responses and subsequently to promote resolution of inflammation. The suppressor of cytokine signaling (SOCS) proteins play a key role in regulating macrophage phenotype. In this review, we summarize research to date from mouse and human studies on the role of the SOCS proteins in determining the phenotype and function of macrophages. We will also touch on the influence of the SOCS on dendritic cell (DC) and microglial phenotype and function. The molecular mechanisms of SOCS function in macrophages and DCs are discussed, along with how dysregulation of SOCS expression or function can lead to alterations in macrophage/DC/microglial phenotype and function and to disease. Regulation of SOCS expression by microRNA is discussed. Novel therapies and unanswered questions with regard to SOCS regulation of monocyte–macrophage phenotype and function are highlighted.